2007
DOI: 10.1021/ol0706197
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Dispersion and Water Solubilization of BODIPY Dyes via Palladium-Catalyzed C−H Functionalization

Abstract: Fluorescent probes 1 and 2 were prepared directly from tetramethyl-BODIPY via palladium-mediated C-H functionalization reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 21 publications
0
64
0
Order By: Relevance
“… aryl substitution at the 3 and/or 5 position (e.g., 2 and 5 ) 7–9 ; ethynylphenyl substitution (e.g., 3 ) 10 ; styryl substitution (e.g., 4 ) 11–16 ; vinyl substitution at the 2 and 6 positions 17 ; aryl substitution at the 1, 3, 5, and 7 positions 18 ; exchange of the meso‐ (8)‐carbon for a nitrogen atom (aza‐BODIPYs) together with 1,3,5,7‐tetraaryl substitution (e.g., 6 ) 19–23 ; aromatic ring fusion (e.g., 7 ) 24,25 ; or combinations thereof. …”
Section: Chemical Modification Strategies Toward Long‐wavelength Bodimentioning
confidence: 99%
“… aryl substitution at the 3 and/or 5 position (e.g., 2 and 5 ) 7–9 ; ethynylphenyl substitution (e.g., 3 ) 10 ; styryl substitution (e.g., 4 ) 11–16 ; vinyl substitution at the 2 and 6 positions 17 ; aryl substitution at the 1, 3, 5, and 7 positions 18 ; exchange of the meso‐ (8)‐carbon for a nitrogen atom (aza‐BODIPYs) together with 1,3,5,7‐tetraaryl substitution (e.g., 6 ) 19–23 ; aromatic ring fusion (e.g., 7 ) 24,25 ; or combinations thereof. …”
Section: Chemical Modification Strategies Toward Long‐wavelength Bodimentioning
confidence: 99%
“…A large number of functional groups can be introduced through well-documented synthetic approaches to the BODIPY core, allowing the preparation of sophisticated dyes with fine-tuned optical, ( photo)physical and chemical properties. In recent years, several reactive BODIPY scaffolds have been reported, which allow a nearly unlimited molecular structural modification, e.g., the use of halogenated BODIPYs,8,9 the Liebeskind-Srogl reaction 10 and direct functionalization (e.g., nucleophilic substitution of hydrogen at the 3,5-positions, 11 direct alkenylation 12 and direct borylation 13 at the 2,6-positions). The parent BODIPY dye shows absorption and emission around 500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Burgess' group has shown that addition of a sulfonate group to the 2- and 6-positions increases aqueous solubility without sacrificing quantum yield 4. They have also made water soluble BDPs for covalent modification of biomolecules and cassettes for energy transfer by appending sulfonic acids to the BDP core and adding carboxylic acid-containing tethers 12, 13. Niu et al have taken a different approach.…”
mentioning
confidence: 99%